Exploitation of Thai Women in Georgia In Vitro Fertilization Practices - Hanifah, Nida Syahla; Prawira, Muhammad Rizki Yudha (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The global rise in assisted reproductive technologies, particularly in vitro fertilization (IVF), has created a transnational market often intertwined with ethical and human rights concerns. Specific Background: In Georgia, weak regulatory frameworks have facilitated exploitative IVF practices involving Thai women, revealing patterns of reproductive trafficking masked as legitimate medical services. Knowledge Gap: While both Thailand and Georgia have ratified international conventions such as CEDAW and the Palermo Protocol, the practical enforcement of these instruments in cross-border IVF contexts remains underexplored. Aims: This study aims to analyze the exploitation of Thai egg donors in Georgia through a human rights lens, identifying legal shortcomings and proposing measures aligned with international norms. Results: Findings indicate that the exploitation constitutes human trafficking under the Palermo Protocol, highlighting a regulatory vacuum that prioritizes commercial profit over women’s bodily autonomy and informed consent. Novelty: The research bridges reproductive ethics, international human rights law, and feminist legal theory to expose how IVF commercialization enables structural gender-based exploitation. Implications: The study underscores the necessity for harmonized transnational regulation, implementation of Mutual Legal Assistance (MLA) frameworks, and adoption of global ethical standards to ensure reproductive justice and protect women from exploitation in assisted reproductive industries. Highlights: Highlights the exploitation of Thai women in Georgia’s IVF industry as a form of human trafficking. Reveals the regulatory vacuum and weak enforcement of international human rights standards. Proposes cross-border legal harmonization through Mutual Legal Assistance (MLA) to protect women’s rights. Keywords: In Vitro Fertilization, Human Trafficking, Egg Donation, Reproductive Rights, Legal Regulation